2014
DOI: 10.1093/ofid/ofu086
|View full text |Cite
|
Sign up to set email alerts
|

Other Respiratory Viruses Are Important Contributors to Adult Respiratory Hospitalizations and Mortality Even During Peak Weeks of the Influenza Season

Abstract: This prospective study conducted during 2 influenza seasons shows that even during the peak weeks of influenza circulation, other respiratory viruses contribute substantially to adult respiratory hospitalizations and mortality and, among the elderly, may exceed influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…Numerous respiratory pathogens are associated with hospitalization; notably, influenza, human metapneumovirus, respiratory syncytial virus, rhinovirus, and parainfluenza virus; all of which cause similar symptoms [3]. However, influenza-associated illness accounts for a substantial proportion of these medical events [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous respiratory pathogens are associated with hospitalization; notably, influenza, human metapneumovirus, respiratory syncytial virus, rhinovirus, and parainfluenza virus; all of which cause similar symptoms [3]. However, influenza-associated illness accounts for a substantial proportion of these medical events [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Human respiratory syncytial virus is considered an important viral agent causing upper respiratory and lower respiratory tract infection, especially in children, the elderly, and immunocompromised adults . Some studies have also shown the importance of RSV as a causative agent of respiratory tract infections in healthy adults, causing significant morbidity …”
Section: Discussionmentioning
confidence: 99%
“…One patient had a dual-positive rapid influenza diagnostic test for influenza A and influenza B, but PCR testing was positive for influenza A (H 3 N 2 ). [2][3][4][5][6] Of the 37 adults with viral ILIs, 16 (43%) had respiratory syncytial virus (RSV), 10 (27%) had rhinovirus/enterovirus (R/E), 5 (14%) had human parainfluenza virus type 3 (HPIV-3), 4 (11%) had human metapneumovirus (hMPV), and 2 (5%) had coronavirus (Table 1). Elderly patients, more commonly admitted for viral ILIs, had longer LOS for viral ILIs than for influenza.…”
Section: Infection Control Implications Of Protracted Lengths Of Staymentioning
confidence: 99%
“…Two patients had co-colonization with influenza A (H 3 N 2 ) and another respiratory virus, but not a worse prognosis. [4][5][6] None of the 37 adults with viral ILIs had bacterial coinfection at admission or during hospitalization.…”
Section: Infection Control Implications Of Protracted Lengths Of Staymentioning
confidence: 99%